TINJAUAN YURIDIS TENTANG PENGATURAN PEMBEBASAN BERSYARAT DALAM SISTEM PERADILAN PIDANA - Hardi Done; Faad Anugrah Moh (Jurnal Ilmu Hukum Kanturuna Wolio, 2026)
This study aims to analyze the regulations regarding parole in the Indonesian criminal justice system, specifically its requirements, procedures, and the role of correctional institutions (Lapas) in their implementation. The study utilizes a normative legal methodology combined with an empirical approach, through a literature review and interviews conducted in the Baubau Class IIA Prison. The study's results indicate that parole is a right of prisoners, as enshrined in Article 15 of the Criminal Code and Law No. 12 of 1995 on Prisons, with substantive requirements such as a minimum sentence of two-thirds (at least nine months), good behavior, active participation in development programs, and community acceptance; as well as administrative requirements in the form of complete legal documents, community investigation reports, behavioral records, and letters of guarantee. The procedure for granting this right is a multi-layered process, starting with the inmate's application, assessment by the prison's observation team, verification by the head of the prison, approval by the regional office of the Ministry of Justice and Human Rights, and ratification by the Directorate General of Prisons. Prisons play a strategic role in the development, feasibility assessment, proposals, and coordination with the Correctional Center for post-release supervision. However, practical implementation faces obstacles, such as limited resources for correctional services and low community acceptance of ex-offenders. Optimizing conditional release therefore requires synergy between prisons, correctional facilities, and the community to achieve the goals of the correctional system, namely social reintegration and recidivism prevention